Kontribusi Madrasah Diniyah Dalam Membentuk Karakter Anak - Indriana, Dina; Saád, Suadi (Tarbawiyah Jurnal Ilmiah Pendidikan, 2021)
The purpose of this study was to determine the contribution of junior high school (madrasah diniyah) to shaping children's character. Madrasah Diniyah (JHS) as an Islamic education institution was established to hold learning activities based on the Islam religion. The students who take part in this school activity start at the age of 8 or those who are already in grade 2 up to the age of 11 or those in grade 5. The research method used in this research was qualitative research. The author's data collection techniques used observations and interviews. The data analysis technique used was through the data reduction stage, data presentation, and drawing conclusions. The results of this study show that most of the children who attend madrasah diniyah (JHS) have noble morals, such as performing religious activities (reciting the Qur'an or praying together known as jamaáh). It can be seen that teenagers in Taman Puri housing complex do prayer together at the mosque, participate in routine recitation studies, study religious books, provide compensation to the poor during the month of Muharram, celebrate the Prophet Muhammad's birthday activities with the community at the mosque, act honest and polite towards elders and so on.